2019
DOI: 10.1097/meg.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution and risk factors of hepatitis B virus and hepatitis C virus infections among thalassemia patients: a regional study

Abstract: Background Thalassemia is a group of inherited hematological disorders caused by mutation in globin’s genes. Regular blood transfusion lengthens the life of thalassemia patients but it carries a definite risk of the infections of blood-borne diseases. Aim/Objective The current study was carried out for the frequency distributions and risk factors of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among thalassemia patients in Hazara regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Pakistan has the second-highest number of HCV cases in the world (>10 million), with a prevalence of 5.9% in the general population [31]. Our results showed a seroprevalence of 26%, though, a variable range of HCV prevalence has been reported in prior studies (5.5% to 68.2%) [19,22,[26][27][28][29][30]. Current prevalence of HCV in TM patients is 13.6% in Iran, 14.7% in Bangladesh and 11-30% in India [32][33][34].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Pakistan has the second-highest number of HCV cases in the world (>10 million), with a prevalence of 5.9% in the general population [31]. Our results showed a seroprevalence of 26%, though, a variable range of HCV prevalence has been reported in prior studies (5.5% to 68.2%) [19,22,[26][27][28][29][30]. Current prevalence of HCV in TM patients is 13.6% in Iran, 14.7% in Bangladesh and 11-30% in India [32][33][34].…”
Section: Discussionsupporting
confidence: 47%
“…Our results showed HBV is the second most common TTI in TM patients with a prevalence of 3.13%, while its reported seroprevalence ranged from 0.66% to 7.4% [19,22,[26][27][28][29][30]. Our findings were similar to the majority of studies [19,22,[26][27][28][29][30], but other studies reported variable results due to variations in the disease prevalence in various regions of the world and non-standardized methods of transfusion in some centers due to lack of facilities. The prevalence of HBV is found to be lower than HCV is likely due to higher rates of immunization against HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Three provinces of Pakistan were represented in the included studies: eight were conducted in Khyber Pakhtunkhwa [18][19][20][21][22][23][24][25], 11 were conducted in Punjab [26][27][28][29][30][31][32][33][34][35][36] and six were conducted in Sindh [37][38][39][40][41][42]. One study was conducted both in Punjab and Khyber Pakhtunkhwa [43] while one was conducted [25]. After reviewing the methodological quality of the studies, 6 were deemed to be of good quality, 21 of medium quality, and no article was found with poor quality.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The articles were published between January 1995 and December 2018 while the period of subject inclusion was from June 1991 to September 2017. Three provinces of Pakistan were represented in the included studies: eight were conducted in Khyber Pakhtunkhwa, 18-25 11 were conducted in Punjab 26-36 and six were conducted in Sindh. 37-42 One study was conducted both in Punjab and Khyber Pakhtunkhwa 43 while one was conducted in Punjab and Sindh.…”
Section: Resultsmentioning
confidence: 99%
“…44 Most of the included studies (20 out of 27) reported HCV prevalence based on the results of the ELISA (enzyme-linked immunosorbent assay) test. 17-20, 22, 25, 26, 28-35, 40-43 Only three studies reported the confirmation of HCV infection by RNA test. 21, 24, 39 Four studies did not report the type of assay used for HCV antibody reactivity testing.…”
Section: Resultsmentioning
confidence: 99%